Thermosensitive liposomes: a promising step toward localised chemotherapy. (3rd August 2022) - Chaudhry, Maryam; Lyon, Paul; Coussios, Constantin; Carlisle, Robert
ABSTRACT: Introduction: Many small molecules and biologic therapeutics have been developed for solid tumor therapy. However, the unique physiology of tumors makes the actual delivery of these drugs into the tumor mass inefficient. Such delivery requires transport from blood vessels, across the vasculature and into and through interstitial space within a tumor. This transportation is dependent on the physiochemical properties of the therapeutic agent and the biological properties of the tumor. It was hoped the application of nanoscale drug carrier systems would solve this problem. However, issues with poor tumor accumulation and limited drug release have impeded clinical impact. In response, these carrier systems have been redesigned to be paired with targetable external mechanical stimuli which can trigger much enhanced drug release and deposition. Areas covered: The pre-clinical and clinical progress of thermolabile drug carrier systems and the modalities used to trigger the release of their cargo are assessed. Expert opinion: Combined application of mild hyperthermia and heat-responsive liposomal drug carriers has great potential utility. Clinical trials continue to progress this approach and serve to refine the technologies, dosing regimens and exposure parameters that will provide optimal patient benefit.